(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation: Since children’s bodies are still growing and developing, any illness can negatively affect their physical and mental development. Therefore, it is important to use natural remedies in the treatment of children, in particular, massage exercises. Massage therapy is widely used to restore a child’s health, normalize muscle activity, and stimulate the nervous and respiratory systems.